(untitled) (Nexus International Journal of Science and Education, 2024)
The mental health stability and stress management of teachers have become increasingly critical topics in the field of education. The respondents of this study were composed of 120 teachers within Maa District, Division of Davao City. The researcher sets the criteria inclusion of respondents. The respondents must be public elementary school teachers, from Maa District, Division of Davao City. This abstract provides a concise overview of the issues, emphasizing their importance and the key strategies for addressing them. Teachers play a pivotal role in shaping the future by educating the next generation, yet they often experience high levels of stress due to various professional challenges. Prolonged exposure to stress can have severe consequences on their mental health, potentially leading to burnout, anxiety, and depression. These adverse effects not only impact teachers personally but also influence their ability to provide effective education to students